Analisis Gaya Kepemimpinan; Tinjauan Teoritis Dalam Islam - Tintin Handiyati; Kun Nurachadijat (Journal on Education, 2023)
In the historical perspective of leadership from an artistic perspective, it can be said that leadership is an art that is as old as humans on earth, which has been practiced throughout human history. Islamic leadership prioritizes the values that are put forward by Islam and also everything that is done because it expects the pleasure of Allah. Islamic leadership is more than part of the goals pursued while in organizational leadership in general, supports the strengthening of the establishment of Islamic order in the organization. Islamic leadership supports absolute leadership or authoritative leadership, this leadership has its own characteristics from leadership in general. The leadership style according to Islam is divided into 5 styles namely Bureaucratic, Permissive, Participatory, Laissez-faire, and Autocratic.